Theory of Mind Abilities and Comprehension of Mental Terms in Subgroups of Children With Autism Spectrum Disorder and Developmental Language Disorder. - Hadad, Eden; Segal, Osnat (Journal of Speech, Language & Hearing Research, 2025)
Purpose: This study examined how subgroups of children with autism spectrum disorder (ASD) and developmental language disorder (DLD) perform on theory of mind (ToM) tasks and comprehend mental terms. Method: Eighty Hebrew-speaking children aged 5--6 years were divided into four groups: children with DLD, ASD and language impairment (ASD-LI), and ASD and typical language abilities (ASD-LN) and typically developing (TD) peers. Language was assessed using the Hebrew Goralnik test. All participants had an average nonverbal IQ (> 85). Comprehension of mental terms, including the factive verb know, the nonfactive verbs think and guess, and the adjective sure, was evaluated contrasting these terms by using 12 paired stimuli organized into three sets. Results: TD children scored highest on the Theory of Mind Task Battery (ToMTB), followed by ASD-LN, ASD-LI, and DLD groups. For factive and nonfactive terms (FNFTs), ASD-LN performed highest, followed by TD, DLD, and ASD-LI. One-way analyses of covariance controlling for nonverbal IQ revealed significant group differences. Pairwise comparisons demonstrated that TD and ASD-LN outperformed ASD-LI and DLD on the ToMTB and FNFTs. Hierarchical regression analysis indicated that both nonverbal intelligence and language ability significantly predicted ToM performance. The addition of FNFT comprehension increased the explanatory power of the model. Conclusions: This study underscores differences in ToM and FNFT comprehension across subgroups and highlights similarities between ASD-LI and DLD. These findings emphasize the strong link between language skills and ToM abilities, with FNFT comprehension playing a crucial role in ToM development.